"Animal spirits" in John Maynard Keynes's general theory of employment, interest and money: Some short and sceptical remarks - Ingo Barens (Technische Universität Darmstadt, Department of Law and Economics, 2011)
The recent global financial crises has caused renewed interest in the economic theories of John Maynard Keynes. In the general public and parts of academe Keynes is seen as the one economist who had very clear knowledge of the instability of markets, the volatility of economic activity and the reasons why these dreadful possibilities become reality - knowledge that mainstream economic theory allegedly has lost in the last decades. In discussions about alternatives to failed mainstream economics the notion (or phrase) 'animal spirits' takes centre stage. Sometimes 'animal spirits' even are set against the 'invisible hand' of Adam Smith as an alternative (and realistic) vision of the working of capitalist economies (Akerlof/Shiller 2010, xxiii). This role of 'animal spirits' in present-day discussions has been magnified by the publication of a book that sets itself the goal of rewriting economic theory under the heading of Keynes's 'animal spirits' that allegedly pervade all economic activity (ibid.). Keynes used the phrase 'animal spirits' only in three passages of The General Theory of Employment, Interest and Money, short passages that do not reveal their meaning immediately or easily. The following remarks try to clarify the meaning, relevance and source (or sources) of Keynes's use of this phrase. The remarks start with a very short sketch of the origin and development of the concept of 'animal spirits' from ancient physiology to modern philosophy. The analytical structure of the General Theory will be discussed in order to understand the relevance of 'animal spirits' for Keynes's critique of the orthodox economics of his day. The next section will then analyse the three passages in which Keynes made use of the concept of 'animal spirits'. The penultimate section addresses the potential source (or sources) of Keynes's use of 'animal spirits'. The final section draws some sceptical conclusions.
Keywords: 330; Sunspot; Dogmengeschichte; Keynesianismus